Surmounting the barricades : women in the Paris Commune - Eichner, Carolyn Jeanne, 1961- (Indiana University Press, 2004)
This book vividly evokes radical women's integral roles within France's revolutionary civil war known as the Paris Commune. It demonstrates the breadth, depth, and impact of communard feminist socialisms far beyond the 1871 insurrection. Examining the period from the early 1860s through that century's end, Eichner investigates how radical women developed critiques of gender, class, and religious hierarchies in the immediate pre-Commune era, how these ideologies emerged as a plurality of feminist socialisms within the revolution, and how these varied politics subsequently affected the fin-de-